Antibiotic Resistance Pattern of Bacterial Clinical Isolates in Tertiary Care Hospital of Nepal: An Observational Study - Karki, Naresh; Prasad, Pravin; Bajracharya, Kishor; Kandel, Kamal; Yadav, Purushottam (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Assessment of antibiotic resistance patterns in hospitals is functional for antibiotic stewardship. This study aims to describe the prevalence of antibiotic resistance patterns of bacterial clinical isolates in a tertiary care hospital. Methods: A cross-sectional study was conducted in the Microbiology Department of Lumbini Medical College and Teaching Hospital, Tansen, Palpa, Nepal, from 13 February 2024 to 6 September 2024 for a seven-month duration after approval from the Institutional Review Committee (Protocol No: IRC-LMC-022/N-23). Data of bacterial clinical isolates from different specimens, such as urine, pus/swab, sputum, and vaginal swab, were collected. Further, data were entered in a pre-designed case proforma, which included information on the types of bacteria causing infections and their antibiotic susceptibility and resistance. Data were expressed in frequency and percentage.Results: A total of 202 bacterial clinical isolates from patients were reviewed. Of the total clinical isolates, 86 (42.6%) were urine specimens. Escherichia coli growth was commonly observed in 76 (37.6%) of various clinical isolates. A total of 1730 antibiotics were tested for culture & sensitivity. Of them, intermediate and resistance were seen in 53 and 804 antibiotics, respectively. The average number of antibiotic resistances was 4.24 ± 3.04. In 171 (84.7%) clinical isolates, resistance was seen in more than one antibiotic. Ampicillin (14.7%) was the most common resistant antibiotic, followed by ciprofloxacin (7.0%).Conclusion: Antibiotic resistance was observed in more than one antibiotic. Thus, this study may help in antibiotic stewardship.